2014
DOI: 10.1080/10962247.2014.992554
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in gas-phase ammonia and PM2.5 ammonium in the Southeast United States

Abstract: Ammonia measurements from the Southeastern Aerosol Research and Characterization (SEARCH) study network were analyzed for trends over 9 yr (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) of observations. Total ammonia concentrations, defined as the sum of gas-phase ammonia and fine particle ammonium, were found to be decreasing by 1-4% yr −1 and were qualitatively consistent with ammonia emission estimates for the SEARCH states of Alabama, Georgia, Mississippi, and Florida. On the other hand, gas-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 47 publications
4
47
0
Order By: Relevance
“…Sulfate wet deposition fluxes and aerosol concentrations both decrease by 6-8 % yr −1 , consistent with the trend in SO 2 emissions (Hand et al, 2012). There is no significant change in NH emissions during this period (Xing et al, 2013;Saylor et al, 2015). However, aerosol ammonium decreases at a rate similar to sulfate (−8.5 % yr −1 ).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Sulfate wet deposition fluxes and aerosol concentrations both decrease by 6-8 % yr −1 , consistent with the trend in SO 2 emissions (Hand et al, 2012). There is no significant change in NH emissions during this period (Xing et al, 2013;Saylor et al, 2015). However, aerosol ammonium decreases at a rate similar to sulfate (−8.5 % yr −1 ).…”
Section: Introductionsupporting
confidence: 59%
“…One would expect from standard sulfate-ammonium thermodynamics that this would result in an increase in the ammonium-sulfate ratio R. However, observations show that the sulfate and ammonium components of the aerosol decreased at similar rates over the period so that R did not increase (Hand et al, 2012;Blanchard et al, 2013;Kim et al, 2015;Saylor et al, 2015;Weber et al, 2016), adding to the thermodynamic puzzle. Weber et al (2016) presented a detailed thermodynamic analysis of 1998-2013 observations of sulfate and ammonium aerosol and gas-phase ammonia at a rural site in the Southeast (Centreville, Alabama).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Energy pricing that has shifted substantial electricity generation from coal to natural gas has also contributed to regional and national air quality improvements [35,36]. Many studies have characterized temporal trends in sulfate, nitrate, ammonium, and carbonaceous compounds-the major components of PM 2.5 mass-across different regions of the US [37][38][39][40][41][42][43][44]. However, due to their typically minor contribution to PM mass, atmospheric trends in transition metals have not been closely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Budisulistiorini et al (2015) also report that no strong relationships were found between IEPOX-SOA formation and particle acidity. With SO 4 concentrations decreasing by more than 80% in much of the eastern United States from the early 1990s to current time periods and ammonia concentrations remaining about the same over the same time period (Saylor et al, 2015;Weber et al, 2016; Acknowledgments…”
mentioning
confidence: 99%